ASSESSMENT OF THE EFFECTIVENESS OF SCHOOL GUIDANCE SERVICES AS PERCEIVED BY SECONDARY SCHOOL PRINCIPALS IN EDO STATE, NIGERIA - Omozele, Beatrice; Toyosi, Nathaniel (International Journal of Research -GRANTHAALAYAH, 2018)
The study investigated the effectiveness of school guidance services as perceived by principals in Edo State, Nigeria. The study sought to examine secondary school principals’ perception on the effectiveness of guidance services (orientation, appraisal, information and counselling services) and determine gender and school location differences in principals’ perception of the effectiveness of counselling services in schools. The descriptive survey design was adopted for the study. A sample of 36 schools (1 rural and 1 urban) were drawn from public senior secondary schools in the study area using purposive random sampling. The instrument used for the collection of data was a self-developed questionnaire titled: “School Guidance Services Effectiveness Questionnaire (SOGSEQ)”. The construct validity was ascertained by the Principal Component Analysis (PCA) while the Cronbach reliability alpha of the questionnaire yielded an overall index of 0.84. The descriptive statistics such as mean (X ̅) and standard deviation (S.D) was used to analyze the research question 1 while the t-test for independent sample means was used to test the hypothesis at 0.05 alpha level. Results from the analysis showed that principals perceived orientation services to be the only effective guidance service in secondary schools in Edo State. Result further showed that there is a significant difference between rural and urban principals in their perception on the effectiveness of school guidance services (appraisal, information and counselling services) in secondary schools in Edo State. It is recommended that guidance counsellors in the secondary schools should realize that their guidance services should be such that will enable them to meet the needs of learners in schools. For this to be achieved, school heads, teachers, parents and the government must also be actively involved in providing their support for the delivery of the services when necessary